Nickel Ferrite/Polyaniline Nanocomposite doped with 2-Naphthalene sulfonic acid as aqueous chromium adsorbent - Brink, Hendrik Gideon (University of Pretoria, 2023)
Dissertation (MEng(Chemical Engineering))--University of Pretoria, 2023.